2015
DOI: 10.1007/s11230-015-9600-1
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Kentropyxia Baker, 1982 parasitic in the small intestine of Osteocephalus taurinus Steindachner (Anura: Hylidae) from the Brazilian Eastern Amazon

Abstract: Kentropyxia hylae n. sp. is described based on material from small intestine of Osteocephalus taurinus Steindachner from Caxiuanã National Forest, municipality of Melgaço, state of Pará, Brazil. The new species is easily distinguished from the type-species and only species of the genus, Kentropyxia sauria Baker, 1982, by its smaller dimensions, the presence of cervical alae, spicules divided into three parts: a robust, single pointed outer processes ending with small finger-like projections and latero-dorsal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…According to Ben Slimane et al (1996), this morphological trait is considered plesiomorphic in Molineidae. Therefore, the position of K. hylae in our phylogeny, the presence of type I bursa and corona radiata in these species reinforce the hypothesis raised by Ben Slimane et al (1996) and Feitosa et al (2015) that Kentropyxia spp. emerged first, before the species of Oswaldocruzia (figs 2 and 3).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to Ben Slimane et al (1996), this morphological trait is considered plesiomorphic in Molineidae. Therefore, the position of K. hylae in our phylogeny, the presence of type I bursa and corona radiata in these species reinforce the hypothesis raised by Ben Slimane et al (1996) and Feitosa et al (2015) that Kentropyxia spp. emerged first, before the species of Oswaldocruzia (figs 2 and 3).…”
Section: Discussionsupporting
confidence: 90%
“…However, we observed that the morphology of molineid nematodes of amphibians seemed to be highly conserved, and despite the cephalic structures, no distinctive ultrastructural characters were observed between the two genera. We also observed the discontinuous nature of the longitudinal ridges, as pointed out by Santos et al (2008); Feitosa et al (2015) and Willkens et al (2016). The ridges seem to occasionally appear and disappear along the body, resulting in a variable number of ridges for both Kentropyxia and Oswaldocruzia .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, using light microscopy, we also observed that the analyzed specimens have a pair of internal bursal papillae and that ray 4 has a medial groove. The presence of a medial groove in ray 4 has also been observed in another Molineidae nematode species by Feitosa et al (2015). This character could be present in all species of the family and should be added to diagnostic traits for the family; however, detailed studies of these species are necessary.…”
Section: Discussionmentioning
confidence: 82%
“…According to Campião et al (2014), almost 92% of anurans in Brazil have not been examined for helminth parasites. Currently, the only nematodes reported to parasitize O. taurinus are Physalopteroides venancioi Lent, Freitas, & Proença 1946, Ochoterenella vellardi Travassos, 1929, and Kentropyxia hylae Feitosa, Furtado, Santos & Melo 2015 (Campião et al , 2014; Feitosa et al , 2015). The present work reports and describes a new species of Parapharyngodon parasite from the large intestines of O. taurinus from the Caxiuanã National Forest, Brazil.…”
Section: Introductionmentioning
confidence: 99%